Percutaneous Balloon Aortic Valvuloplasty (Pbav) in a Child With Congenital Severe Aortic Stenosis A Case Report - Reza, AQM; Patwary, MSR; Baqui, A (Cardiovascular Journal, 2011)
A 8 years old boy presented with shortness of breath, cough and palpitation and subsequently diagnosed as a case of severe aortic stenosis with bicuspid aortic valve. Percutaneous balloon aortic valvuloplasty (PBAV) was done and he became asymptomatic. Post procedure his aortic valve area and aortic systolic pressure increased, transaortic pressure gradient decreased. So good result, lower cost, elimination of drawbacks of thoracotomy and cardiopulmonary bypass suggest in children percutaneous balloon aortic valvuloplasty should be the treatment of choice for patients with severe aortic stenosis. Key Words: Percutaneous balloon aortic valvuloplasty, Severe aortic stenosis, Bicuspid aortic valve DOI: http://dx.doi.org/10.3329/cardio.v1i2.8241 Cardiovasc. j. 2009; 1(2): 234-236